Crack Detection of Reinforced Concrete Member Using Rayleigh-Based Distributed Optic Fiber Strain Sensing System - Tingjin Liu; Honghao Huang; Yubing Yang (Advances in Civil Engineering)
Early detection of crack is critical for the maintenance of reinforced concrete (RC) structures. In this study, a distributed optical fiber (DOF) sensing system with Rayleigh Optical Frequency Domain Reflectometry (OFDR) technique was deployed to a member of RC structure in a full-scale laboratory experiment, which was subjected to a monotonic lateral load. With the aid of a high space resolution (up to 1 mm) and measurement accuracy (±1 micro strain) interrogator (OSI-S by Semicon), continuous strain measurements inside of the RC member are elaborately implemented. The result of crack detection by the analysis of the measured tensile strain profiles is in excellent agreement with the visually observable cracks mapped during the test. This confirms the ability of the optical fiber inside of RC members to capture cracks on concrete surface. Moreover, the recognition of crack orientation and depth is accomplished by comparing strain measurements of optical fibers installed at multiple locations.